Rice Leaf Extract for Kidney Damage Prevention in Plumbum-Exposed Rats - Budi Santosa; Henna Ria Sunoko; Andri Sukeksi (Universitas Muhammadiyah Semarang, 2016)
Abstract. Plumbum (Pb) is a heavy metal affecting renal tubular epithelial cells and causing necrosis. This study aimedto demonstrate the effectiveness of rice leaf extract in degeneration and necrosis prevention of renal tubule epitheliumexposed to lead. Twenty eight rats were divided into a control and 3 treatment groups all exposed to Pb by 0.5 g/ kg/ day,but only the treatment groups had received rice leaf extract in varied doses for 8 weeks. Results from Kruskal-Wallis andsphearman rho tests showed that the number of normal cells, degeneration and necrosis were significantly different (0.03;0.05; 0.04) between control and treatment groups with a strong positive correlation of treatment (r = 0.97) in normal cellsand a strong negative one in cell degeneration and necrosis. (R = -0.92 and r = -0.93). As conclusion, rice leaf extractshowed ability in the prevention of kidney damage in rats exposed to lead.